Derivatization-Based Liquid Chromatography-Tandem Mass Spectrometry Method for Quantification of Folate Species: A Cost-Effective Method for the Health Food Industry - Wang, Hung-Cheng; Yamamoto, Atsushi; Chang, Yongjin; Kawai, Yasushi; Rakhimuzzaman, Md; Emi, Takashi (ACS food science & technology, 2025)
Folates are crucial for one-carbon (C1) metabolism, with C1-modified tetrahydrofolate (C1-THF) exhibiting superior functionality. However, analysis of these compounds is challenging because of their low stability. This study presents a novel chemical derivatization-based liquid chromatography-tandem mass spectrometry (LC-MS/MS) method that stabilizes folates and the synthesis of internal standards (IS) for precise quantification. Six folate species were identified in autolyzed yeast extract (AYE). Following derivatization with 2-methylpyridine–borane complex and acetaldehyde, distinct derivatives of C1-THF and other folate species were produced. IS were synthesized from specific folate species using the same derivatization technique, by replacing acetaldehyde with acetaldehyde-d4. Recovery percentages for four spiking folate species in AYE at three concentration levels ranged from 95 to 104%. With derivatization and deconjugation, the total folate content was 408 ± 15 μg/100 g, in which C1-THFs dominated. This proposed method is convenient and cost-effective for precise quantification of folates based on their functionalities.